2006
DOI: 10.1103/physreve.74.026101
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-mass multifractal analysis of river networks and braided channels

Abstract: A fixed-mass multifractal (FMA) analysis was used to investigate natural river networks and braided channels. In particular, while the study of natural river networks was performed with fixed-size algorithms (FSAs) in the past, the analysis of natural braided channels was not pursued before to our knowledge. Results showed the multifractal and non-plane-filling nature of all the digitalized data sets. Analysis of the digitalization step (constant or not) was performed and showed that it does not exert a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…It is important to highlight that the interpretation of the results provided so far is in perfect agreement with the results obtained by De Bartolo, Primavera, et al (), in the context of the characterization of multifractal spectra related to streams of different Horton‐Strahler orders, the network for which has been extracted from digitized maps on a 1:25,000 scale.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is important to highlight that the interpretation of the results provided so far is in perfect agreement with the results obtained by De Bartolo, Primavera, et al (), in the context of the characterization of multifractal spectra related to streams of different Horton‐Strahler orders, the network for which has been extracted from digitized maps on a 1:25,000 scale.…”
Section: Resultssupporting
confidence: 86%
“…Besides these traditional approaches, the multifractal measures have been characterized by considering the distribution of points defining the geometry of a generic set on a fractal or multifractal support (see, e.g., Harte, ; Olsen, ). Following these ideas, De Bartolo et al () and De Bartolo, Primavera, et al () applied multifractal techniques to analyze the geometry of the river networks. These studies demonstrated that the characterization of fluvial structures by net − points and specifically their measure (see next section) can be considered as a fluvial geomorphological magnitude like the other ones mentioned previously.…”
Section: Methodsmentioning
confidence: 99%
“…The investigation includes analysis of the sewer network geometry and distribution of imperviousness derived from available GIS data, including the way in which it is represented in operational semi-distributed hydrodynamic urban drainage models. In order to be able to use the same technique to analyse both sewer networks and maps of distributed imperviousness, we use fractal tools on them, and not multifractal ones such as the one found in De Bartolo et al (2004Bartolo et al ( , 2006 for river networks. Multifractals will be used in the characterization of the representation of imperviousness in models.…”
Section: Introductionmentioning
confidence: 99%
“…Other multifractal studies include those of DeBartolo et al . () on river networks and braided channels, Roy and Padhi () on earthquakes in Iran, García‐Marín et al . () on validating a rainfall model, and Movahed and Hermanis () and Zhang et al .…”
Section: Introductionmentioning
confidence: 99%